Evaluación de la harina de tomillo (Thymus vulgaris l.) (al 5, 10 y 15 %) como promotor de crecimiento en cerdos mestizos en la parroquia la Victoria, del cantón Pujilì - Jiménez Jiménez, Marco Javier (2015)
Thyme Flour has compounds such as: thymol, carvacrol, borneol, linaol, among others. They have properties that act as: digestive, antiseptic, vermifuge, antispasmodic, eupéptico, carminative. Also, it increases appetite. So. It promotes digestión and leukocytes activity and as a sedative in coughing crisis. For all this, it is considered as a growth promoter. This research was developed in Pujilí, La Victoria Town. It spent 120 days. The study goal was on Thyme flour evaluation (5, 10 and 15%). These percentages are based on thyme toxicity. Well, this is a mestizo pigs growth’ promotor. The pigs were evaluated on their increased weight and height; FCR Mortality - Morbidity and cost / benefit. The selection was 16 castrated male pigs mestizos with 45 days old. They were divided into 4 compartments, of 4 animals groups. They were selected in random. They were identified in many treatments….